Justification of the architecture of environmental monitoring systems - Kuziev, Zokir; Yusupbekov, Nadirbek; Gulyamov, Shuxrat; Mirzaev, Dilshod (AIP conference proceedings, 2024)
The information technologies for monitoring the environment of an industrial zone using Arduino, JavaScript, NodeJS, HTML and CSS have been presented, which allowed us to develop an appropriate software and hardware complex for real-time monitoring in the modern concept of the Internet of Things. The use of the complex as a prototype for the organization of monitoring in dynamically changing environments and in critical situations has been clarified. This Complex can be used as a prototype for the organization of monitoring in dynamically changing environments and in critical situations. The following subsystems are included in the software and hardware complex: - data accumulation. This subsystem combines remote automated workstations of the subjects of the common monitoring system, which collect data and transmit it via certain communication (network) protocols to the control system center. - info communications. This subsystem is a synthesis of modern productive and reliable backend, high-speed communication networks (including WSN) and communication protocols. As part of the software and hardware complex, it provides data reception from automated workstations, their processing and recording in the appropriate databases, effective communication with a separate information and analytical center, as well as with management decision makers, etc.